2019
DOI: 10.1152/jn.00310.2019
|View full text |Cite
|
Sign up to set email alerts
|

Between-hand coupling during response inhibition

Abstract: Response inhibition reflects the process of terminating inappropriate preplanned or ongoing movements. When one hand is cued to stop after preparing a bimanual response (Partial trial), there is a substantial delay on the responding side. This delay is termed the interference effect and identifies a constraint that limits selective response inhibition. γ-Aminobutyric acid (GABA)-mediated networks within primary motor cortex (M1) may have distinct roles during response inhibition. In this study we examined whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Despite the prevalent interference in the EMG at the group level, the single-trial ∆peak indicated large variability, including trials with no interference. This is in line with previous findings showing that interference can be eliminated under specific conditions (Xu et al, 2015) or when a small delay is required between the bimanual left and right hand responses (in contrast to simultaneous ones), which necessitates a decoupling of the bimanual response (Wadsley et al, 2019). These results highlight that the stop-restart behavior in the bimanual stop signal task is not mandatory, but a preferred option when selectivity is not incentivized by the task requirements.…”
Section: Single Inhibition Mechanism With Predominantly Global Extentsupporting
confidence: 92%
“…Despite the prevalent interference in the EMG at the group level, the single-trial ∆peak indicated large variability, including trials with no interference. This is in line with previous findings showing that interference can be eliminated under specific conditions (Xu et al, 2015) or when a small delay is required between the bimanual left and right hand responses (in contrast to simultaneous ones), which necessitates a decoupling of the bimanual response (Wadsley et al, 2019). These results highlight that the stop-restart behavior in the bimanual stop signal task is not mandatory, but a preferred option when selectivity is not incentivized by the task requirements.…”
Section: Single Inhibition Mechanism With Predominantly Global Extentsupporting
confidence: 92%
“…This difference is not necessarily surprising as SSRT in Partial Stop trials is more than a measure of pure (or global; i.e stop everything) inhibitory network activity. The stop cue on these trials triggers a sequential non-selective stop, response uncouple, reprogram, then selective go process(Coxon et al, 2007; MacDonald et al, 2012; MacDonald et al, 2014; Cowie et al, 2016; Wadsley et al, 2019; MacDonald et al, 2021) which leads to the delayed RT. Partial RI SSRT therefore reflects a complex series of neural processes which are triggered by the partial stop cue and involve interactions between facilitatory and inhibitory prefrontal-basal ganglia networks (Coxon et al, 2009; Coxon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because some, or all, of the sequential process captured by the SSRT (stop, uncouple, reprogram, then go) occurred over a shorter time scale in session two. The overall time required for this process can be reduced on Partial Stop trials of both the ARIT (Wadsley et al, 2019) and SST (Xu et al, 2014) through manipulations to overall task design. Wadsley and colleagues (2019) increased the asynchrony between left and right-side components of the default response, thereby reducing the amount of time needed for response uncoupling during partial RI and reducing the stopping interference effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations